Nursing care for arteriovenous fistula (Research, Society and Development, 2024)
Chronic diseases significantly affect patients' daily lives, among which we highlight renal insufficiency. Hemodialysis (HD) is the most common dialysis method. There are various types of vascular accesses, including temporary ones such as central venous catheters (CVC) and permanent ones such as Arteriovenous Fistula (AVF), the latter indicated only for chronic renal patients. This study aimed to highlight, through scientific literature, nursing care for patients with Arteriovenous Fistula. It is a descriptive bibliographic study conducted in the Scielo and Bireme databases, where 10 articles were selected after cross-referencing and applying inclusion and exclusion criteria. From the information gathered, it was possible to highlight that the main care for AVF includes assessing thrill, collapse, signs of infection, avoiding measuring blood pressure on the AVF limb, not drawing blood through the fistula, avoiding wearing accessories like watches, and preventing trauma to the limb. During HD sessions, the complications observed were hematoma or extravasation, needle dislodgment during the dialysis session, high venous pressure in the fistula, pain, decreased or absent thrill, bleeding, AVF rupture, difficult needle puncture due to clots. Nurses play a crucial role in caring for these patients, as they empower them in self-care.